UMP announcement system via GSM - Norsuhada, Khosni (2011)
In this globalization era,people tend to use a mobile phone as a way of communication that gives those benefits as a reminder or personal assistant.Class Schedule via Mobile (CSM)by Using Simulator is developed to help the users in future which are going to be implemented in a mobile phone, in order to give and show the class schedule besides of personal information and class notification.This is as a new improvement from the existing system or manual method.This new approach would ease them in teaching and learning process at UMP.CSM by Using Simulator is run in a simulator, soon can be deployed in a Smartphone.The system is using the web service to connect with the web page.CSM by Using Simulator is applying System Development Life Cycle as a development methodology (SDLC). It is created with Visual Studio 2008 that designed for the user interface; while SQL SERVER 2005 is a platform for the data recorded and also by using the Windows Mobile Smartphone simulator in the Visual Studio 2008. CSM by Using Simulator is believed would be able to meet the user's requirements with the profit it gives.